Family-Based Self-Management Model for Improving Hypertension Control among Older Adults in the Community - Ririn Safitri; Naomi Malaba (Jurnal Ilmu Kesehatan Nusantara, 2025)
Background: Hypertension is a major chronic health problem among older adults and requires continuous self-management. Age-related limitations may reduce medication adherence, healthy lifestyle practices, and regular blood pressure monitoring. Family participation can support older adults in managing hypertension at home. Research Objective: This study aimed to evaluate the effectiveness of a Family-Based Self-Management Model in improving self-management behaviour and hypertension control among older adults in the community. Methods: This quasi-experimental study used a pretest–posttest control-group design. Forty-two older adults with hypertension were selected through purposive sampling and allocated to intervention and control groups, with 21 participants in each group. The intervention was implemented for eight weeks. Data were analysed using paired and independent t-tests, with statistical significance set at p < 0.05. Results: The intervention group demonstrated a significant increase in self-management scores from 52.38 to 73.71 (p < 0.001). Mean systolic and diastolic blood pressure decreased by 20.86 and 10.19 mmHg, respectively. After the intervention, 66.7% of participants in the intervention group achieved controlled hypertension, compared with 23.8% in the control group (p = 0.005). Conclusion: The Family-Based Self-Management Model effectively improved self-management behaviour, medication adherence, and blood pressure control among older adults. Its integration into community hypertension programmes is recommended.